VARIATION IN THE SIZE OF ABDOMINAL AORTA MEASURED ON COMPUTED TOMOGRAPHY - Sharma, Dolly; T, Visakh (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The normal size of the abdominal aorta is expected to be <3 cm though the size changes with age as well as workload. There is a need to know the variation in size of the abdominal aorta to avoid the formation of aneurysm and further complications. Materials and Methods: This study was carried out at Kasturba Medical College after taking 130 patients considering the inclusion and exclusion criteria. 130 patients who all came for abdomen computed tomography (CT) were divided into 65 patients in each age group under 20–40 years and 40–80 years. The measurements of abdominal aorta were anteroposterior (AP) and right left (RL) measured at T12-L1 level on plain axial abdomen CT images on Extended Brilliance Workstation. Result: We observed that there was a statistical significant difference in the average AP diameter between the two age groups (p<0.001). Another finding was a statistical significant difference in the average RL diameter between the two age groups (p<0.001), and, hence the size of abdominal aorta varies with age. Conclusion: The proposed study concluded that there was variation in the size of abdominal aorta with age. These findings would be helpful in early detecting of aneurysm and in avoiding aortic dissection.